Calculation of the Raman frequencies and thermodynamic quantities at high pressures for the cubic gauche nitrogen (cg-N) - AKAY, ÖZGE (My University, 2023)
This study gives the calculation of the frequencies from the V-P Vinet EOS which has been modified as the frequency-pressure (υ-P) relation for the spectroscopic parameters in the cubic gauche nitrogen(cg-N). Calculation of the Raman frequencies is performed by means of the mode Grüneisen parameter as a function of pressure for the cg-N phase. From the Raman frequencies calculated, the pressure dependence of the thermodynamic quantities such as the free energy, entropy, heat capacity and the enthalpy are predicted by using the quasi-harmonic approximation for the cg-N structure. Our results show that the υ-P relation derived from the V-P relation (Vinet-EOS) can be used to predict the frequencies and that the quasi-harmonic approximation is satisfactory to predict the thermodynamic quantities of interest, as exemplified for the cg-N structure in this study.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; cg-N structure; Mode Grüneisen parameter; Raman frequencies; Thermodynamic quantities; υ-P relation